2020
DOI: 10.1111/rec.13283
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic invertebrate assemblages as potential indicators of restoration conditions in wetlands of Northeastern China

Abstract: Wetland restoration has been implemented widely but evaluation of the effectiveness of wetland restoration has been limited. In this study, we aimed to investigate the utility of aquatic invertebrate assemblages as potential indicators of restoration condition in wetlands of the Sanjiang Plain, Northeastern China. Results from non‐metric multidimensional scaling analysis of invertebrate assemblages showed that study wetlands (n = 16) divided into two groups: natural wetlands and wetlands that have been restore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Odonata) and are predators, with reference sites reflect their greater maturity and structural complexity (Coccia et al., 2016), providing more oviposition sites and prey. Other studies elsewhere showed predominance of high dispersal taxa in new restored ponds (Barnes, 1983; Kim et al., 2014; Lu et al., 2021; Ruhí et al, 2013). Although communities in both wetland types are largely re‐assembled through colonization from nearby permanent wetlands, new ponds are more dominated by early colonizers whose movement from one new pond to another could be enhanced either by their homogeneous environmental conditions or their spatial configuration.…”
Section: Discussionmentioning
confidence: 84%
“…Odonata) and are predators, with reference sites reflect their greater maturity and structural complexity (Coccia et al., 2016), providing more oviposition sites and prey. Other studies elsewhere showed predominance of high dispersal taxa in new restored ponds (Barnes, 1983; Kim et al., 2014; Lu et al., 2021; Ruhí et al, 2013). Although communities in both wetland types are largely re‐assembled through colonization from nearby permanent wetlands, new ponds are more dominated by early colonizers whose movement from one new pond to another could be enhanced either by their homogeneous environmental conditions or their spatial configuration.…”
Section: Discussionmentioning
confidence: 84%
“…For instance, Stewart and Schriever [5] investigated the relative effects of environmental and spatial factors on the beta diversity of aquatic macroinvertebrate assemblages across 36 interdunal wetlands from five freshwater dune complexes in two eco-regions spanning a latitudinal gradient across Lake Michigan. Other researchers have also studied the potential utility of aquatic invertebrate communities as indicators of the wetland restoration status in the Sanjiang Plain in northeastern China [144] and the paucity of plant species in a Danish wetland 17 years after restoration [4].…”
Section: Indicator Species Approachmentioning
confidence: 99%
“…For instance, a restored stream in China showed almost 50% of the taxa found in a natural undisturbed stream after about 4 years also occurred in a restored stream. Specific species of damselfly and biting midges were found to be good indicators of the restoration success (Lu et al, 2021). In other cases, crustaceans have been used along with fish, to assess restoration efforts.…”
Section: Aquatic Species and Restoration Effortsmentioning
confidence: 99%